Protection of medical data within the scope of the Law on Protection of Personal Data - Çiftçi, Özge Dirim (Bioethica, 2022)
As a result of non-stop developing technology, each corner of our lives become more and more reachable. Although privacy has always been very valuable and modern laws has taken steps to provide security of privacy, nowadays it takes only some seconds to reach the surname, workplace, the address etc of a person; even of a family. Although some may believe sharing information is harmless, from spam emails to obsessive stalking there is not an actual limit of what can be done with wrongly accessed personal data. When having frequent commercial calls from firms or missing your important mails because of the commercials that fill your mail box, we experience that even the slightest privacy violation can be very annoying. However some personal data are exactly what people face discrimination of. In todays world it is common to see people are discriminated due to their religion, sexuality, politic views, past convictions and even due to their health conditions. The results of discriminations may vary from not being included to social life to mobbing at work; in some extreme cases it may even put the persons life at risk by making them a target. Considering the possible risks and the easiness to reach, as technology has been developing constantly, the need for data protection is more visible than ever. This article aims to explain the protection of medical data in Turkish Legislation by focusing on Law on Protection of Personal Data.